The Relationship Between Latrine Ownership and Open Defecation Behavior in Kebagusan Subdistrict, Pasar Minggu - Pou, Rudy; Apriliana, Dian Nur; Ramdhan, Rizal Maulana; Riskawa, Risna M (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
According to the Weekly Epidemiological Record (2013), Indonesia ranked second globally in the number of people practicing open defecation. By 2019, around 20.44% of Indonesian households lacked septic tanks for final fecal disposal. In Kebagusan Subdistrict, located in the Pasar Minggu area, the prevalence of open defecation was recorded at 7.68%. This study employed a quantitative analytic method with a cross-sectional design. A total of 179 respondents were selected using purposive sampling. Data were analyzed using the Chi-square test (X²) and presented through narrative descriptions, tables, and pie charts. The dominant age group was 31–45 years (41.9%). Educational attainment among respondents included senior high school (48.6%), elementary school (17.3%), junior high school (16.8%), higher education (14.0%), and those who did not complete elementary school (3.4%). As many as 74.9% of respondents were categorized as low-income. Most used private latrines (87.7%), while 10.6% had no latrine, and 1.7% used shared facilities. Open defecation was reported by 43.6% of respondents. Regarding knowledge, 50.8% were classified as having good knowledge, though 52.5% demonstrated negative attitudes. Significant relationships were found between age, knowledge, and latrine ownership with open defecation behavior (p = 0.000; p = 0.033; p = 0.000, respectively). The findings suggest that open defecation in the Pasar Minggu community is influenced by being in the productive age group, having lower education levels, and inadequate fecal waste management evident in the fact that one-third of latrine owners lacked septic tanks.